Tryptophan metabolism in brain tumors: IDO and beyond - Platten, Michael; Friedrich, Mirco; Wainwright, Derek A.; Panitz, Verena; Opitz, Christiane (Current opinion in immunology, 2021)
Metabolism of the essential amino acid tryptophan is a key metabolic pathway that restricts antitumor immunity and is a drug development target for cancer immunotherapy. Tryptophan metabolism is active in brain tumors including gliomas and promotes a malignant phenotype and contributes to the immunosuppressive tumor microenvironment. In recent years, improved understanding of the regulation and downstream function of tryptophan metabolism has been significantly expanded beyond the initial in vitro observation that the enzyme indoleamine-2,3-dioxygenase 1 (IDO1) promotes the depletion of intracellular tryptophan. Here, we revisit the specific roles of tryptophan metabolites in regulating brain functioning and neuronal integrity as well as in the context of brain tumors. This review summarizes recent developments in identifying key regulators, as well as the cellular and molecular effects of tryptophan metabolism with a particular focus on potential therapeutic targets in glioma